The Resistance Mechanism of Mycoplasma bovis From Yaks in Tibet to Fluoroquinolones and Aminoglycosides - Niu, Jiaqiang; Yan, Mingshuai; Xu, Jinhua; Xu, Yefen; Chang, Zhenyu; Sizhu, Suolang (Frontiers in Veterinary Science, 2022)
In order to investigate the resistance mechanism of Mycoplasma bovis from yak in Tibet to aminoglycoside and fluoroquinolone. analysis of fluoroquinolones . We found that three isolated strains had resistance to ciprofloxacin, two isolated strains had resistance to spectinomycin and norfloxacin, one isolated strain had resistance to gentamicin and enrofloxacin, and the isolated strains were relatively sensitive or not resistant to kanamycin. We have induced 9 highly resistant strains to aminoglycosides which resistant to one aminoglycoside by in vitro induce were also showing a cross-resistance to the other two aminoglycosides. There were no base mutations in target genes for Sensitive strains and resistant strains while 9 highly resistant strains induced in vitro have bases mutations in target genes (rrs 3 and rrs 4): 3 strains that are highly resistant to gentamicin have a base mutation of A1409T in rrs 3 and rrs 4; 3 strains that are highly resistant to kanamycin have a base mutation of A1408G in rrs 3 and rrs 4; 1 strain that is highly resistant to spectinomycin has a base mutation of C1192T in rrs 3 and rrs 4, and 2 strains has a base mutation of C1192T in rrs 3; Whereas, no significative mutation was detected in rps E (encode ribosome protein S5). 9 strains of Mycoplasma bovis that are stable and resistant to one fluoroquinolone antibiotic were selected by in vitro induction, and there was cross-resistance to the other two fluoroquinolone antibiotics. Sensitive strains have non-significant amino acid mutations (Asp84) in the target gene (par C). there is a single-site amino acid mutation (Ser 83 Phe/Tyr, Ser 80 Ile/Arg, or Ser 81 Phe) in the target gene (gyr A or par C) for resistant strains to fluoroquinolone antibiotics; in vitro induced highly resistant strains, there are amino acid mutations (Ser83Phe and Ser80Ile) in the target genes (gyr A and par C); the amino acid mutations at the relevant sites were not detected in the target genes gyr B and par E. The research can provide a reference for clinical treatment of Mycoplasma bovis and related research on the resistance mechanism.